La dramatización y el desarrollo de la autoestima en los niños de cinco años del salón loritos de la I.E.I. N° 602 Primavera del distrito de San Juan Bautista 2023 - Vela Guerra, Ani Michell (2024)
The main objective of the study was to determine the relationship between dramatization and self-esteem in 5-year-old children in the Loritos classroom of the I.E.I. Nº. 602 “Spring” of the San Juan Bautista district 2023. In terms of its approach, the research adopted a quantitative perspective and, in terms of its categorization, is classified as a correlational study. The population included all five-year-old children in IEI Nº. 602 “Primavera” of the San Juan Bautista district during the year 2023, totaling 90 children. The sample, for its part, was made up of 5-year-old children belonging to said institution. A sampling method was not used since we worked with the entire population, and a random selection method was not necessary because it was a census study, that is, with each study subject. The instrument for obtaining data was the observation sheet. In the most relevant results, it is observed that the level of dramatization of 50.0% (45) of the children presented a good level of dramatization, 28.9% (26) of the children presented a regular level of dramatization and 21.1% (19) of the children had poor dramatization level respectively. Thus, demonstrating that 54.4% (49) of the children presented a high level of self esteem, 37.8% (34) of the children presented a medium level of self-esteem and 7.8% (7) of them presented a low level of self-esteem respectively.